Model Pembelajaran E-Learning (LMS) Untuk Meningkatkan Pemahaman Materi Termodinamika Teknik - Sumardi, Kamin; Supriawan, Dedi (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2011)
The purpose of this research is to produce an e-learning teaching model in order to enhance to comprehension of the thermodynamic technology. There are to main activities, i.e.: identifying the need of teaching material (including the data of category and the topics of suitable lecture material for e-learning, and the pedagogic aspects) and making the e-learning model. Our research subjects are 84 students of mechanical engineering department FPTK UPI who has taken thermodynamic technology lecture. The results of this research are as follows: (a) The LMS (e-learning) thermodynamic technology becomes the centre of student activities (community web based distance learning); (b) Interaction in the student groups, through discussion; and (c) The student administrations system, including attendance, tasks, tests and achievement will be more complete, various and up to date. The research results concerning the thermodynamic technology material are as follows: (a) new information; (b) clear teaching goal formulation; (c) integration between new substance content with loose lecture material; (d) students can show the level of their comprehension through exercise; (e) the concise, short, and compact material explanation; (f) feedback against the evaluation conducted.